The Abstention of Urban Students Preference in Indonesian Election 2024 - Henky Fernando; Yuniar Galuh Larasati; Irwan Abdullah; Putri Ananda Saka; Muhammad Hendri; Leanne Morin (Politicon : Jurnal Ilmu Politik, 2024)
This study aims to identify the potential and preferences for abstention by urban students as young voters in the 2024 elections in Indonesia. This context tends to be ignored in previous studies that discuss the phenomenon of abstention in general elections. In addition to responding to the shortcomings of previous studies, this study also focuses on the characteristics and preferences underlying urban students as young voters choose to abstain in the 2024 general election in Indonesia. The findings in this study show that the age characteristics of urban students in the Yogyakarta area tend to choose to abstain from voting and appear in the productive age range of around 20 years from 27 provinces of origin. In addition to appearing with such complex characteristics, the behaviors of urban students who tend to abstain are also influenced by the dominant political preferences of their social structure, access to information, and their perceptions of the ongoing democratic system in the 2024 general elections in Indonesia. From these findings, it can be reflected that the abstention of urban students as young voters is not only temporal but also a rational choice of the regulatory system and the democratic process in such a complex general election.